Identifying the Behavioral and Functional Components of Urban Management on Improving Urban livability (Case Study: Ahvaz Metropolis) - Maleki 1, Saeed; Amanpour 2*, Saeed; Firoozi 1, Mohammad Ali; Rohani-Rasaf 3, Mohammad Reza (Shahroud Journal of Medical Sciences, 2020)
Background: According to many problems in contemporary cities, the emphasis is on new approaches and approaches to urban development and the creation of a favorable link between the urban environment and social life through the enhancement of the components of urban livability. The aim of the study was to identify the effective components of behavioral and functional good urban governance on promoting urban livability in the Ahvaz metropolitan area.Methods: This study is a descriptive-analytical type. The statistical population of the study consisted of Ahvaz metropolitan citizens (1302591 persons) and academic professors and elites. The sample size of the citizens was 383 based on the Cochran model and the sample size of academic professors and elites was 100 people based on the Delphi method. The t-test in SPSS 23 software and Structural Equation Modeling (SEM) based on partial least squares (PLS) were used for data analysis.Results: The most desirable indicators of urban livability were recreation, leisure and public transport and the lowest desirable indicators were employment, income, environmental sustainability, and personal and social security. Also, among the components of behavioral and functional good urban governance, the highest impact on the promotion of the urban livability related to justice, transparency and responsibility were 0.753, 0.704 and 0.632, respectively. The Goodness of Fit (GOF) of models was found to be 0.513 which indicates the overall utility of the model.Conclusions: The results show that Ahvaz metropolis is in poor condition in terms of components of good governance and urban livability.Keywords: Behavioral and Functional Components, Good Urban Governance, Livability, Ahvaz Metropolis.